Opportunities and Limitations in Developing Thailand’s International Rail Freight Transport Law to Align with International Railway Law - Umpai, Kiarttiphorn (Nitipat NIDA Law Journal, 2026)
International railway freight transportation plays a crucial role in economic integration within the ASEAN region, yet continues to face significant obstacles due to inconsistent legal frameworks among member countries. This research aims to analyze opportunities and constraints in developing Thailand’s international railway carriage contract law to align with international legal principles and ASEAN regional cooperation frameworks. The study employs comparative legal analysis methodology, examining two major legal systems: the European COTIF/CIM system and the Eurasian OSJD/SMGS system, compared with Thailand’s domestic law and ASEAN cooperation frameworks. The research encompasses analysis of carrier liability, transportation documentation requirements, dispute resolution mechanisms, and liability limitations. Research findings reveal that Thailand lacks comprehensive legislation specifically addressing international railway freight carriage, while ASEAN has yet to establish binding common legal frameworks. However, opportunities exist for developing domestic legislation aligned with international standards through adaptation of OSJD/SMGS principles, given that several ASEAN countries are already members of this system. The research recommends that Thailand develop specific railway carriage contract legislation, promote cooperation with ASEAN countries in establishing regional agreements, and consider joining OSJD membership to prepare for future international railway system connectivity.